MORTALITAS LARVA NYAMUK Aedes aegypti (Cullicidae: Diptera) INSTAR III YANG DIKOLEKSI DARI KELURAHAN LOA BAKUNG, DADI MULYA DAN SEMPAJA TIMUR KOTA SAMARINDA TERHADAP ABATE - Febritasari, Tya; Hariani, Nova; Trimurti, Sus (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
Dengue fever dengue (DBD) is an infectious disease caused by dengue virus, which is spread by the Aedes aegypti mosquito. Samarinda City health report that the last 3 years of disease in some wards DBD Samarinda endemic status and has an incidence rate 155,1/100,000 population. The village has a number of cases most of which political districts Loa Bakung, Dadi Mulya and East Sempaja. One of the controls is done by sharing Samarinda Health Office to the public, however abate insecticide control using abate hasn’t been able to reduce the number of cases of illness DBD. This research aims to know the mortality of larvae of the mosquito Ae. aegypti (Diptera: Cullicidae) of abate relic Loa Bakung, Dadi Mulya and East Sempaja,Samarinda. Methods used namely ovitrap method and analysis software with POLO-PC. From the 3 region value of LC50 obtained abate with the dose 0.01% recommended by the Health Office RI is no longer effective because the results showed that abate 0.01% can't kill animals testing by 50% in a span of 24 hours.